Harvesting system established for the utilisation of Miscanthus sinensis ‘tatai’ “energy cane” in biomass power plants - Pintér, Csaba (Acta Agraria Debreceniensis, 2016)
The increasing demand for energy worldwide and the resulting environmental impacts of fossil fuels forced many countries to turn to renewable energy resources as a clean and sustainable alternative. More than a third of Europe’s binding renewable energy source target of 20% by 2020 will come from solid biomass for electricity and heating according to the National Renewable Energy Action Plans submitted by member states of the European Union (EU) to the European Commission. To achieve this goal long-term yield studies in renewable energy plants are important to determine mean annual biomass and energy yield, and CO2 emission. Field experiments worldwide and also in Europe have demonstrated that Miscanthus, a fast-growing C4 rhizomatous grass can produce some of the highest biomass and energy yield per hectare of all potential energy plants. Miscanthus is a plant that originates from the southern slopes of the Himalayas. It was bred for the Hungarian climatic conditions in 2006 under the name of Miscanthus sinensis ‘Tatai’ (MsT). The species has high frost and drought tolerance and high energy value. This is why there is growing demand for the biomass (lignocellulose) produced by growing this plant. The biomass, produced from the high yield energy reed, can be transported to power plants in large quantities, in forms of bales. Its household consumption is not yet significant. This study presents the external features, characteristics, propagation and plantation process of MsT energy reed. The study also demonstrates the harvest technology of the species worked out between 2009–2012 in Tata, Hungary and the options of supplying to biomasspower stations.